Oxygen evolution electrode loaded with high-entropy layered hydroxide catalyst and preparation method of oxygen evolution electrode

Through the preparation method of oxygen evolution electrodes supported by high entropy layered hydroxide catalysts, the problems of instability and insufficient activity of the existing catalysts are solved by using electrodeposition technology and surfactant, and efficient and stable water electrolytic catalytic effect is achieved.

CN120193295APending Publication Date: 2025-06-24TONGJI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510371549.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-06-24

AI Technical Summary

Technical Problem

The existing water electrolytic catalysts have problems such as unstable crystal structure and element dissolution during the electrolysis process, and the traditional bimetal hydroxide catalysts have insufficient catalytic activity, poor structural stability, and complex preparation process.

Method used

Using the preparation method of oxygen evolution electrodes loaded with high entropy layered hydroxide catalyst, the high entropy layered hydroxide catalyst is rapidly grown in situ on the substrate of the gas diffusion layer through electrodeposition technology to form a stable three-phase reaction interface, reduce interface impedance, and achieve uniform elements mixing and interface buffering through surfactants.

Benefits of technology

It improves the activity and stability of the catalyst, reduces the elementary reaction barrier during the OER reaction, optimizes kinetics, extends the electrode life, simplifies the preparation process, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120193295A_ABST
    Figure CN120193295A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water electrolysis hydrogen production, in particular to an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst and a preparation method of the oxygen evolution electrode. Comprising the following steps: S1, pretreating a gas diffusion layer substrate; s2, hydrolyzable transition metal element salt, a surfactant and a pH regulator are mixed with water, an electrochemical deposition solution is obtained, and more than or equal to four transition metal elements are contained in the hydrolyzable transition metal element salt; and S3, constructing a two-electrode or three-electrode system by taking the gas diffusion layer substrate pretreated in the step S1 as a working electrode, and carrying out electro-deposition reaction in the electrochemical deposition solution obtained in the step S1 to obtain the oxygen evolution electrode loaded with the high-entropy layered hydroxide catalyst. Compared with the prior art, the preparation method has the advantages that the activity and stability of the electrode material can be considered, and the oxygen evolution electrode with a stable structure can be obtained under the condition of ensuring good activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen production by electrolyzing water, and in particular to an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst and a preparation method thereof. Background Art

[0002] In recent years, the global science and technology and economic levels have grown rapidly, and the global energy demand has surged. Hydrogen energy is a flexible, efficient, green, low-carbon, and widely used secondary energy source, and is currently gradually becoming one of the important carriers for the global energy transformation and development. Water electrolysis driven by renewable energy is a favorable way to sustainably produce hydrogen, and this process includes an oxygen evolution reaction (OER) and a hydrogen evolution reaction (HER). At present, there is still a large room for improvement in the energy efficiency of water electrolysis. Developing and using more efficient catalysts can further reduce the overpotential, promote the generation of hydrogen and oxygen at a lower voltage, improve the electrolysis efficiency, and thus further reduce the hydrogen production cost.

[0003] Layered hydroxide materials represented by layered double metal hydroxides (LDH) have many advantages such as low price, simple synthesis, easy modulation of the composition and structure, and rich active sites, and show good application prospects in the fields of electrochemistry and electrocatalysis. However, at present, such materials still have problems such as unstable crystal structure and element dissolution during the water electrolysis process, and the introduction of ionomers during the electrode preparation process also results in low utilization rate of the active sites of the materials. Due to their unique physical and chemical properties such as high entropy effect, cocktail effect, and sluggish diffusion effect, high-entropy materials (HEM) are now attracting more and more attention from researchers, and high-entropy modification methods have increasingly become an effective means to improve the stability of materials and increase the activity of materials. Existing high-entropy materials are mostly prepared by methods such as mechanical alloying (high-energy ball milling), hydrothermal method, and melting metallurgy. These methods usually have defects such as long preparation cycle, high large-scale production cost, and easy environmental pollution. And traditional binary layered hydroxide catalysts (such as NiFe-LDH) also have a series of problems such as insufficient catalytic activity, poor structural stability, and complex preparation process.

[0004] Patent Publication No. CN114921803A discloses a preparation method and application of a transition metal sulfide composite hydroxide electrode. This method uses the hydrothermal method to load transition metal sulfides on a conductive substrate, and then uses the hydrothermal method or electrodeposition method to in-situ grow transition metal hydroxides on the transition metal sulfides to obtain a transition metal sulfide composite hydroxide electrode. This preparation method enhances the stability and conductivity of the hydroxide by constructing a heteroepitaxial growth substrate (sulfide and hydroxide). The preparation process is cumbersome, and the transition metal sulfide may be oxidized or corroded in a strong alkaline electrolyte, especially during long-term operation at a high potential, which may lead to the degradation of the sulfide layer and affect the long-term stability of the electrode. Summary of the Invention

[0005] The object of the present invention is to overcome the defects of the above-mentioned existing technologies and provide an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst and a preparation method thereof, which takes into account both the activity and stability of the electrode material, and can obtain an oxygen evolution electrode with a stable structure while ensuring good activity.

[0006] The object of the present invention can be achieved by the following technical solutions:

[0007] On the one hand, the present invention provides a preparation method of an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst, comprising the following steps:

[0008] S1. Pretreat the gas diffusion layer (GDL) substrate;

[0009] S2. Mix a hydrolyzable transition metal element salt, a surfactant, and a pH regulator with water to obtain an electrochemical deposition solution, wherein the transition metal element in the hydrolyzable transition metal element salt is greater than or equal to four;

[0010] S3. Use the gas diffusion layer substrate pretreated in step S1 as the working electrode, construct a two-electrode or three-electrode system, and perform an electrodeposition reaction in the electrochemical deposition solution obtained in step S1 to obtain an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst.

[0011] Further, in step S1, the pretreatment steps are: soak the gas diffusion layer substrate in hydrochloric acid, wash with water to remove the residual hydrochloric acid on the surface, soak in ethanol and ultrasonicate, and dry, and the pretreatment is completed.

[0012] Furthermore, the concentration of the hydrochloric acid is 0.1-5M, the solid-liquid ratio of the soaking is 1g:50-200ml, it is necessary to ensure that all the diffusion layer substrates are completely immersed in the acid, and the soaking time is 5-30min to remove the surface oxides.

[0013] Furthermore, the soaking time in ethanol is 5-30min.

[0014] Furthermore, the drying temperature is 40-80°C.

[0015] Further, in step S2, the hydrolyzable transition metal element salt includes but is not limited to nitrates, chlorides, sulfates, acetates, and polyacids; the transition metal elements are selected from at least four of manganese, iron, cobalt, nickel, copper, zinc, chromium, magnesium, aluminum, vanadium, titanium, rhodium, molybdenum, tungsten, lanthanum, cerium, and ruthenium. The above transition metal elements are not exhaustive, and the remaining transition metal elements are also within the protection scope of the present invention.

[0016] Furthermore, the molar content ratio of each transition metal is 10%-40%.

[0017] Furthermore, in step S2, the surfactant includes but is not limited to polyethylene glycol (PEG), sodium dodecyl sulfate (SDS), polyvinylpyrrolidone (PVP), cetyltrimethylammonium bromide (CTAB). Adding a surfactant during the electrodeposition process can balance the deposition rates of different metal ions through complexation, avoid element segregation, and achieve atomic-level uniform mixing of high-entropy components. At the same time, during the electrodeposition process, surfactant molecules can also form a buffer layer at the interface between the catalyst and the substrate, relieve the stress concentration during the electrodeposition process, prevent the catalyst from peeling off after deposition, and improve the loading firmness of the electrode catalyst.

[0018] Furthermore, in step S2, the pH regulator includes but is not limited to potassium acetate, sodium acetate, potassium citrate, sodium citrate, potassium oxalate, sodium glycinate;

[0019] The pH of the electrochemical deposition solution is 4.0 - 6.0.

[0020] Furthermore, in step S2, the molar mass ratio of the hydrolyzable transition metal element salt to the surfactant is 1 mol: 1 - 10 g;

[0021] The concentration of the hydrolyzable transition metal element salt is 0.05 - 0.5 M;

[0022] The concentration of the surfactant is 0.2 - 2 g / L.

[0023] Furthermore, in step S3, when constructing a two-electrode system, the counter electrode used is a graphite electrode or a platinum metal electrode, the electrodeposition process is a constant current chronopotentiometry method, the current is 80 - 140 mA / cm, and the electrodeposition time is 200 - 1000 s;

[0024] When constructing a three-electrode system, the reference electrode used is an Ag / AgCl electrode, the electrodeposition process is a constant voltage chronopotentiometry method, the voltage is -0.9 - -1.5 V, and the electrodeposition time is 200 - 1000 s.

[0025] Through electrodeposition, the rapid in-situ growth of the high-entropy layered hydroxide catalyst on the conductive substrate is realized, a bonding interface is formed, the interface contact resistance is reduced, and the charge transfer is accelerated. At the same time, the catalyst / conductive substrate interface prepared by rapid deposition has the advantage of a self-supporting structure, eliminating the need for additional binders or ionomers, avoiding the coverage of active sites, and enhancing the mechanical stability.

[0026] Furthermore, in step S3, after the electrodeposition reaction, the reacted electrode is washed with water and ethanol, and after drying, an oxygen evolution electrode loaded with the high-entropy layered hydroxide catalyst is obtained.

[0027] On the other hand, the present invention also provides an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst, which is prepared by the above preparation method.

[0028] Further, the oxygen evolution electrode includes a gas diffusion layer substrate and a high-entropy layered hydroxide catalyst loaded on the gas diffusion layer substrate. The loaded high-entropy layered hydroxide catalyst is prepared by electrodeposition and grows in-situ on the gas diffusion layer substrate to form an integrated self-supporting oxygen evolution electrode.

[0029] Further, the high-entropy layered hydroxide catalyst loaded is a two-dimensional layered nanostructured hydroxide containing transition metal elements, and the transition metal elements are selected from at least four of manganese, iron, cobalt, nickel, copper, zinc, chromium, magnesium, aluminum, vanadium, titanium, rhodium, molybdenum, tungsten, lanthanum, cerium, ruthenium.

[0030] Even further, the chemical formula of the high-entropy layered hydroxide catalyst can be expressed as M1M2…M n (OH) x (An) y ·mH2O (M1, M2, …M n are different transition metal elements; An is an intercalated anion, and the specific type depends on the hydrolyzable transition metal element salt; n is the number of transition metal element types, x is the normalized number of bonded hydroxide ions, y is the normalized number of intercalated anions, and m is the normalized number of hydrated water molecules). A high-entropy system is formed by introducing four or more transition metal elements.

[0031] Further, the high-entropy layered hydroxide catalyst has a two-dimensional layered nanostructure.

[0032] Further, the gas diffusion layer substrate includes, but is not limited to, nickel felt, nickel foam, titanium felt, and titanium foam.

[0033] Compared with the prior art, the present invention has the following advantages:

[0034] 1) Benefiting from the unique physical and chemical properties of high-entropy materials, such as the high-entropy effect, lattice distortion effect, and cocktail effect, the high-entropy layered hydroxide catalyst modified by high entropy can form a local stress field, enhance the adsorption / desorption ability of reaction intermediates, and effectively reduce the elementary reaction barrier during the OER reaction process; the multi-element synergistic effect and the participation of lattice oxygen in the catalytic reaction can ensure that the deposited high-entropy layered hydroxide catalyst has excellent catalytic performance. Compared with traditional double-metal hydroxides (such as NiFe-LDH), the atomic radius difference of multi-metal elements leads to lattice distortion, which can form a local stress field. The participation of lattice oxygen in the catalytic reaction and the enhanced adsorption / desorption ability of reaction intermediates can effectively promote the progress of elementary reactions during the oxygen evolution reaction (OER), thereby optimizing the OER reaction kinetics; at the same time, due to the synergistic effect between different transition metal elements, the cocktail effect is formed, which can also significantly improve the overall catalytic performance. In addition, the high-entropy effect can also inhibit the selective dissolution of a single metal during electrolysis and extend the electrode life.

[0035] 2) While ensuring excellent catalytic performance, the high-entropy effect can also effectively reduce the Gibbs free energy of the system, ensure the thermodynamic stability of the material components, play a role in hindering the dissolution of elements and the diffusion of oxygen free radicals, and greatly enhance the stability of the electrode and the entire cell.

[0036] 3) Electrochemically depositing the catalyst on the surface of the gas diffusion layer substrate in-situ and rapidly can bond the catalyst to the conductive substrate in-situ, form a stable three-phase reaction interface, effectively reduce the interfacial impedance between the catalyst layer and the gas diffusion layer, and at the same time can form a low-resistance interface and a self-supporting structure, improve the charge transfer efficiency and mechanical stability, reduce the use of ionomers and the loss of catalyst raw materials during the electrode preparation process. The surfactant can achieve uniform mixing of elements by complexing metal ions and form a buffer layer at the interface to prevent peeling caused by stress concentration and strengthen the loading firmness of the catalyst, further ensuring the structural stability of the electrode. In the present invention, a surfactant is added during the electrodeposition process, and the introduction of sulfides is not required, thereby reducing the deposition steps and simplifying the preparation process, making the preparation of the electrode material simpler and faster. At the same time, the surfactant can also stabilize the growth stability of the high-entropy layered hydroxide, regulate the contact interface between the catalyst and the conductive substrate, so that the prepared oxygen evolution electrode loaded with the high-entropy layered hydroxide catalyst can simultaneously possess high catalytic activity, stability, and conductivity.

[0037] 4) Compared with the traditional electrode production process, the process of preparing the oxygen evolution electrode in one step by the electrodeposition technology described in this application is simple, can effectively shorten the electrode preparation cycle and simplify the preparation process. Moreover, the process described in this application is green and environmentally friendly, easy to scale up production, has certain economic and environmental benefits, and has broad application prospects.

[0038] 5) The integrated porous electrode of the self-supported catalyst for the load is generally regarded as an electrode with considerable development potential in the field of hydrogen production by electrolyzing water. This type of electrode usually does not require an ionomer to anchor the catalyst, thus avoiding a series of problems brought about by the selection of the ionomer. At the same time, the integrated preparation strategy also helps to directly regulate the components and structure of the catalyst, and construct catalysts including ordered nanoarray structures, ordered carrier transport networks, and ordered component designs, etc., which has great prospects for development and utilization. The present invention rapidly prepares an oxygen evolution electrode loaded with a novel high-entropy layered hydroxide catalyst for alkaline water electrolysis by a one-step electrodeposition method. By directly regulating the high-entropy catalyst components and the ordered structure, excellent catalytic performance and good catalytic stability are achieved. Description of the Drawings

[0039] Figure 1 It is a schematic flow chart of the preparation method of the oxygen evolution electrode loaded with the high-entropy layered hydroxide catalyst of the present invention;

[0040] Figure 2 It is a schematic diagram of the crystal lattice structure of the high-entropy layered hydroxide catalyst shown in Example 1;

[0041] Figure 3 It is the X-ray diffraction pattern of the oxygen evolution electrode shown in Example 1;

[0042] Figure 4 It is the scanning electron microscope image of the oxygen evolution electrode shown in Example 1. (a) The magnification is 10,000 times, and (b) the magnification is 40,000 times;

[0043] Figure 5 It is the FESEM EDS-mapping image of the oxygen evolution electrode shown in Example 1. The scale in the figure is 2μm. (a) FESEM image, (b) EDS-mapping image of the O element in the FESEM image, (c) EDS-mapping image of the Mn element in the FESEM image, (d) EDS-mapping image of the Fe element in the FESEM image, (e) EDS-mapping image of the Ni element in the FESEM image, (f) EDS-mapping image of the Co element in the FESEM image;

[0044] Figure 6 It is the XPS images of each element of the oxygen evolution electrode shown in Example 1. (a) Ni element, (b) Mn element, (c) Fe element, (d) Co element;

[0045] Figure 7 It is the linear sweep voltammetry test curve of the oxygen evolution electrodes shown in Examples 1-7;

[0046] Figure 8Linear sweep voltammetry test curves of the oxygen evolution electrodes shown in Example 1 and Comparative Examples 1, 2, and 5;

[0047] Figure 9 Stability test curves of the oxygen evolution electrodes shown in Examples 1-7, (a) Example 1, (b) Example 2, (c) Example 3, (d) Example 4, (e) Example 5, (f) Example 6, (g) Example 7;

[0048] Figure 10 Stability test curves of the oxygen evolution electrodes shown in Example 1 and Comparative Examples 1, 2, and 5, (a) Example 1, (b) Comparative Example 1, (c) Comparative Example 2, (d) Comparative Example 5. Detailed implementation mode

[0049] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments. This embodiment is implemented on the premise of the technical solution of the present invention, and the detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments. Based on the given embodiments, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the scope of protection of this application.

[0050] Unless otherwise specified, the reagents, methods, instruments, and equipment used in the present invention are conventional reagents, methods, instruments, and equipment in the art.

[0051] Example 1

[0052] A preparation method of an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst, as Figure 1 shown, includes the following steps:

[0053] S1. Pretreat the gas diffusion layer substrate.

[0054] Immerse a nickel felt substrate with a size of 5 cm × 5 cm in 1 M hydrochloric acid for 10 min, wash away the residual hydrochloric acid on the surface with deionized water, soak and ultrasonically clean it with ethanol for 10 min, take it out and bake it in an oven at 60 °C for 30 min to obtain a pretreated nickel felt substrate. The nickel felt substrate is purchased from Stanford Advanced Materials, and the model is MF5825.

[0055] S2. Mix a hydrolyzable transition metal element salt, a surfactant, and a pH regulator with water to obtain an electrochemical deposition solution.

[0056] Weigh 14.54 g of nickel nitrate hexahydrate, 12.55 g of manganese nitrate tetrahydrate, 14.55 g of cobalt nitrate hexahydrate, and 9.94 g of ferrous chloride tetrahydrate into 500 ml of deionized water respectively, and stir well until completely dissolved. Under magnetic stirring conditions, add potassium acetate powder to the solution in small amounts and multiple times. During this period, use a pH meter to track and measure the pH value of the solution until the pH is adjusted to 4.5. Continue to add 0.2 g of polyethylene glycol 6000 to the solution under magnetic stirring conditions and stir until completely dissolved to obtain an electrochemical deposition solution. The polyethylene glycol 6000 is purchased from Sinopharm Chemical Reagent Co., Ltd., with a CAS number of 25322 - 68 - 3 and a purity of GR grade.

[0057] S3. Use the gas diffusion layer substrate pretreated in step S1 as the working electrode to construct a three - electrode system, and perform an electrodeposition reaction in the electrochemical deposition solution obtained in step S1 to obtain an oxygen evolution electrode loaded with a high - entropy layered hydroxide catalyst.

[0058] Use the pretreated nickel felt substrate as the working electrode, a graphite rod as the counter electrode, and an Ag / AgCl electrode as the reference electrode for constant - voltage chrono - electrodeposition. The deposition conditions are a voltage of - 1 V vs Ag / AgCl and a deposition time of 300 s. Take out the working electrode after deposition, rinse it with deionized water and ethanol for 10 min respectively, and then dry it naturally to obtain an oxygen evolution electrode loaded with a NiFeCoMn high - entropy layered hydroxide catalyst. The graphite rod is purchased from PalmSens Electrochemical Workstation (Palmsens B.V., Netherlands), with a model of BASi MW - 4131; the Ag / AgCl electrode is purchased from Palmsens B.V., with a model of BASiRE - 5B.

[0059] Example 2

[0060] A preparation method of an oxygen evolution electrode loaded with a high - entropy layered hydroxide catalyst, comprising the following steps:

[0061] S1. Pretreat the gas diffusion layer substrate.

[0062] Immerse a nickel felt substrate with a size of 3 cm × 3 cm in 1 M hydrochloric acid for 10 min, wash away the residual hydrochloric acid on the surface with deionized water, soak it in ethanol and ultrasonically clean it for 10 min, and then take it out and bake it in an oven at 60 °C for 30 min to obtain a pretreated nickel felt substrate.

[0063] S2. Mix a hydrolyzable transition metal element salt, a surfactant, and a pH regulator with water to obtain an electrochemical deposition solution.

[0064] Weigh 8.72 g of nickel nitrate hexahydrate, 7.53 g of manganese nitrate tetrahydrate, 8.73 g of cobalt nitrate hexahydrate, 5.96 g of ferrous chloride tetrahydrate, and 12 g of chromium nitrate nonahydrate separately into 300 ml of deionized water, and stir well until completely dissolved. Under magnetic stirring conditions, add potassium acetate powder to the solution in small portions multiple times, and during this period, use a pH meter to track and measure the pH value of the solution until the pH is adjusted to 5.0. Continue to add 0.2 g of polyethylene glycol 6000 to the solution under magnetic stirring conditions and stir until completely dissolved to obtain an electrochemical deposition solution.

[0065] S3. Using the gas diffusion layer substrate pretreated in step S1 as the working electrode, construct a three-electrode system, and perform an electrodeposition reaction in the electrochemical deposition solution obtained in step S1 to obtain an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst.

[0066] Using the pretreated nickel felt substrate as the working electrode, a graphite rod as the counter electrode, and an Ag / AgCl electrode as the reference electrode for constant voltage chrono-electrodeposition, with the deposition conditions being a voltage of -1V vs Ag / AgCl and a deposition time of 300 s. Take out the working electrode after deposition, rinse it with deionized water and ethanol for 10 min respectively, and then dry it naturally to obtain an oxygen evolution electrode loaded with a NiFeCoMn high-entropy layered hydroxide catalyst.

[0067] Example 3

[0068] A preparation method of an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst, comprising the following steps:

[0069] S1. Pretreat the gas diffusion layer substrate.

[0070] Immerse a nickel felt substrate with a size of 5 cm × 5 cm in 1 M hydrochloric acid for 10 min, wash away the residual hydrochloric acid on the surface with deionized water, soak it in ethanol and ultrasonically clean it for 10 min, and then take it out and bake it in an oven at 60 °C for 30 min to obtain a pretreated nickel felt substrate.

[0071] S2. Mix hydrolyzable transition metal element salts, a surfactant, and a pH regulator with water to obtain an electrochemical deposition solution.

[0072] Weigh 21.81 g of nickel nitrate hexahydrate, 18.83 g of manganese nitrate tetrahydrate, 21.83 g of cobalt nitrate hexahydrate, and 14.91 g of ferrous chloride tetrahydrate separately into 500 ml of deionized water, and stir well until completely dissolved. Under magnetic stirring conditions, add potassium acetate powder to the solution in small portions multiple times, and during this period, use a pH meter to track and measure the pH value of the solution until the pH is adjusted to 4.5. Continue to add 0.2 g of polyethylene glycol 6000 to the solution under magnetic stirring conditions and stir until completely dissolved to obtain an electrochemical deposition solution.

[0073] S3. Use the gas diffusion layer substrate pretreated in step S1 as the working electrode, construct a three-electrode system, and perform an electrodeposition reaction in the electrodeposition solution obtained in step S1 to obtain an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst.

[0074] Use the pretreated nickel felt substrate as the working electrode, a graphite rod as the counter electrode, and an Ag / AgCl electrode as the reference electrode for constant voltage chrono-electrodeposition. The deposition conditions are a voltage of -1.2 V vs Ag / AgCl and a deposition time of 500 s. Take out the working electrode after deposition, rinse it with deionized water and ethanol for 10 min respectively, and then dry it naturally to obtain an oxygen evolution electrode loaded with a NiFeCoMn high-entropy layered hydroxide catalyst.

[0075] Example 4

[0076] A method for preparing an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst, comprising the following steps:

[0077] S1. Pretreat the gas diffusion layer substrate.

[0078] Immerse a nickel felt substrate with a size of 1 cm × 1 cm in 1 M hydrochloric acid for 10 min, wash away the residual hydrochloric acid on the surface with deionized water, soak it in ethanol and ultrasonically clean it for 10 min, and then take it out and bake it in an oven at 60 °C for 30 min to obtain a pretreated nickel felt substrate.

[0079] S2. Mix a hydrolyzable transition metal element salt, a surfactant, and a pH regulator with water to obtain an electrodeposition solution.

[0080] Weigh 5.81 g of nickel nitrate hexahydrate, 4.83 g of copper nitrate trihydrate, 5.82 g of cobalt nitrate hexahydrate, and 3.97 g of ferrous chloride tetrahydrate into 100 ml of deionized water respectively, and stir well until completely dissolved. Add potassium acetate powder to the solution in small portions under magnetic stirring, and use a pH meter to track and measure the pH value of the solution during this process until the pH is adjusted to 5.0. Then continue to add 0.1 g of sodium dodecyl sulfate to the solution under magnetic stirring and stir until completely dissolved to obtain an electrodeposition solution. The sodium dodecyl sulfate is purchased from Shanghai Macklin Biochemical Co., Ltd., with a CAS number of 151-21-3 and a purity of LR grade.

[0081] S3. Use the gas diffusion layer substrate pretreated in step S1 as the working electrode, construct a three-electrode system, and perform an electrodeposition reaction in the electrodeposition solution obtained in step S1 to obtain an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst.

[0082] Using the pretreated nickel felt substrate as the working electrode, a graphite rod as the counter electrode, and an Ag / AgCl electrode as the reference electrode, constant voltage chrono - electrodeposition was carried out. The deposition conditions were a voltage of - 1V vs Ag / AgCl and a deposition time of 300s. After the deposition was completed, the working electrode was taken out and rinsed with deionized water and ethanol for 10 minutes respectively, and then dried naturally to obtain an oxygen evolution electrode loaded with NiFeCoCu high - entropy layered hydroxide catalyst.

[0083] Example 5

[0084] A method for preparing an oxygen evolution electrode loaded with a high - entropy layered hydroxide catalyst, comprising the following steps:

[0085] S1. Pretreat the gas diffusion layer substrate.

[0086] The nickel felt substrate with a size of 5cm×5cm was immersed in 1M hydrochloric acid for 10 minutes, the residual hydrochloric acid on the surface was washed away with deionized water, then immersed in ethanol and ultrasonically cleaned for 10 minutes, and after being taken out, it was baked in an oven at 60℃ for 30 minutes to obtain the pretreated nickel felt substrate.

[0087] S2. Mix hydrolyzable transition metal element salts, surfactants, and pH regulators with water to obtain an electrochemical deposition solution.

[0088] Weigh 14.54g nickel nitrate hexahydrate, 12.55g manganese nitrate tetrahydrate, 14.55g cobalt nitrate hexahydrate, and 9.94g ferrous chloride tetrahydrate into 500ml of deionized water respectively, and stir well until completely dissolved. Under magnetic stirring, potassium acetate powder was added to the solution in small amounts and multiple times. During this period, the pH value of the solution was measured with a pH meter until the pH was adjusted to 4.5. Then, 0.25g of polyethylene glycol 6000 was added to the solution under magnetic stirring and stirred until completely dissolved to obtain the electrochemical deposition solution.

[0089] S3. Using the gas diffusion layer substrate pretreated in step S1 as the working electrode, construct a two - electrode system, and carry out an electrodeposition reaction in the electrochemical deposition solution obtained in step S1 to obtain an oxygen evolution electrode loaded with a high - entropy layered hydroxide catalyst.

[0090] Using the pretreated nickel felt substrate as the working electrode and a graphite rod as the counter electrode for constant - current chrono - electrodeposition, the deposition conditions were a current of 100mA / cm² and a deposition time of 300s. After the deposition was completed, the working electrode was taken out and rinsed with deionized water and ethanol for 10 minutes respectively, and then dried naturally to obtain an oxygen evolution electrode loaded with NiFeCoMn high - entropy layered hydroxide catalyst.

[0091] Example 6

[0092] A method for preparing an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst, comprising the following steps:

[0093] S1. Pretreat the gas diffusion layer substrate.

[0094] Immerse a nickel felt substrate with a size of 5 cm × 5 cm in 1 M hydrochloric acid for 10 min, wash away the residual hydrochloric acid on the surface with deionized water, soak it in ethanol and ultrasonically clean it for 10 min, and then bake it in an oven at 60 °C for 30 min to obtain a pretreated nickel felt substrate.

[0095] S2. Mix a hydrolyzable transition metal element salt, a surfactant, and a pH regulator with water to obtain an electrochemical deposition solution.

[0096] Weigh 14.54 g of nickel nitrate hexahydrate, 12.55 g of manganese nitrate tetrahydrate, 14.55 g of cobalt nitrate hexahydrate, 9.94 g of ferrous chloride tetrahydrate, 12.08 g of copper nitrate trihydrate, 8.97 g of zinc sulfate monohydrate, and 7.89 g of sodium metavanadate dihydrate into 400 ml of deionized water, and stir well until completely dissolved. Under magnetic stirring, add potassium acetate powder to the solution in small portions and measure the pH value of the solution with a pH meter until the pH is adjusted to 5.0. Continue to add 0.05 g of polyethylene glycol 6000 to the solution under magnetic stirring and stir until completely dissolved to obtain an electrochemical deposition solution.

[0097] S3. Use the gas diffusion layer substrate pretreated in step S1 as the working electrode to construct a three-electrode system, and perform an electrodeposition reaction in the electrochemical deposition solution obtained in step S1 to obtain an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst.

[0098] Use the pretreated nickel felt substrate as the working electrode, a graphite rod as the counter electrode, and an Ag / AgCl electrode as the reference electrode for constant voltage chrono-electrodeposition. The deposition conditions are a voltage of -1 V vs Ag / AgCl and a deposition time of 300 s. Take out the working electrode after deposition, rinse it with deionized water and ethanol for 10 min respectively, and then dry it naturally to obtain an oxygen evolution electrode loaded with a NiFeCoMnCuZnV high-entropy layered hydroxide catalyst.

[0099] Example 7

[0100] A method for preparing an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst, comprising the following steps:

[0101] S1. Pretreat the gas diffusion layer substrate.

[0102] Soak a nickel felt substrate with a size of 3 cm × 3 cm in 1 M hydrochloric acid for 10 min, wash away the residual hydrochloric acid on the surface with deionized water, soak it in ethanol and ultrasonically clean it for 10 min, take it out and bake it in an oven at 60 °C for 30 min to obtain the pretreated nickel felt substrate.

[0103] S2. Mix a hydrolyzable transition metal element salt, a surfactant, and a pH regulator with water to obtain an electrochemical deposition solution.

[0104] Weigh 14.54 g of nickel nitrate hexahydrate, 12.55 g of manganese nitrate tetrahydrate, 14.55 g of cobalt nitrate hexahydrate, 9.94 g of ferrous chloride tetrahydrate, 12.08 g of copper nitrate trihydrate, 8.97 g of zinc sulfate monohydrate, and 7.89 g of sodium metavanadate dihydrate into 400 ml of deionized water, and stir well until completely dissolved. Under magnetic stirring, add potassium acetate powder to the solution in small portions and measure the pH value of the solution with a pH meter until the pH is adjusted to 5.0. Continue to add 0.5 g of polyethylene glycol 6000 to the solution under magnetic stirring and stir until completely dissolved to obtain an electrochemical deposition solution.

[0105] S3. Use the gas diffusion layer substrate pretreated in step S1 as the working electrode to construct a three-electrode system, and perform an electrodeposition reaction in the electrochemical deposition solution obtained in step S1 to obtain an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst.

[0106] Use the pretreated nickel felt substrate as the working electrode, a graphite rod as the counter electrode, and an Ag / AgCl electrode as the reference electrode for constant voltage chrono-electrodeposition. The deposition conditions are a voltage of -1 V vs Ag / AgCl and a deposition time of 300 s. Take out the working electrode after deposition, wash it with deionized water and ethanol for 10 min respectively, and then dry it naturally to obtain an oxygen evolution electrode loaded with a NiFeCoMnCuZnV high-entropy layered hydroxide catalyst.

[0107] Comparative Example 1

[0108] A method for preparing an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst, without adding a surfactant in step S2, includes the following steps:

[0109] S1. Pretreat the gas diffusion layer substrate.

[0110] Soak a nickel felt substrate with a size of 5 cm × 5 cm in 1 M hydrochloric acid for 10 min, wash away the residual hydrochloric acid on the surface with deionized water, soak it in ethanol and ultrasonically clean it for 10 min, take it out and bake it in an oven at 60 °C for 30 min to obtain the pretreated nickel felt substrate.

[0111] S2. Mix the hydrolyzable transition metal element salt and the pH regulator with water to obtain an electrochemical deposition solution.

[0112] Weigh 14.54 g of nickel nitrate hexahydrate, 12.55 g of manganese nitrate tetrahydrate, 14.55 g of cobalt nitrate hexahydrate, and 9.94 g of ferrous chloride tetrahydrate into 500 ml of deionized water respectively, and stir well until completely dissolved. Under magnetic stirring, add potassium acetate powder to the solution in small portions and multiple times. During this period, use a pH meter to track and measure the pH value of the solution until the pH is adjusted to 4.5 to obtain an electrochemical deposition solution.

[0113] S3. Use the gas diffusion layer substrate pretreated in step S1 as the working electrode to construct a three - electrode system, and perform an electrodeposition reaction in the electrochemical deposition solution obtained in step S1 to obtain an oxygen evolution electrode loaded with a high - entropy layered hydroxide catalyst.

[0114] Use the pretreated nickel felt substrate as the working electrode, a graphite rod as the counter electrode, and an Ag / AgCl electrode as the reference electrode for constant - voltage chrono - electrodeposition. The deposition conditions are a voltage of - 1 V vs Ag / AgCl and a deposition time of 300 s. Take out the working electrode after deposition, rinse it with deionized water and ethanol for 10 min successively, and then dry it naturally to obtain an oxygen evolution electrode loaded with a NiFeCoMn high - entropy layered hydroxide catalyst.

[0115] Comparative Example 2

[0116] A preparation method of an oxygen evolution electrode loaded with a layered hydroxide catalyst includes the following steps:

[0117] S1. Pretreat the gas diffusion layer substrate.

[0118] Immerse a nickel felt substrate with a size of 5 cm×5 cm in 1 M hydrochloric acid for 10 min, wash away the residual hydrochloric acid on the surface with deionized water, soak it in ethanol and ultrasonically clean it for 10 min, then take it out and bake it in an oven at 60 °C for 30 min to obtain a pretreated nickel felt substrate.

[0119] S2. Mix the hydrolyzable transition metal element salt, the surfactant, and the pH regulator with water to obtain an electrochemical deposition solution.

[0120] Weigh 14.54 g of nickel nitrate hexahydrate and 9.94 g of ferrous chloride tetrahydrate into 500 ml of deionized water respectively, and stir well until completely dissolved. Under magnetic stirring, add potassium acetate powder to the solution in small portions and multiple times. During this period, use a pH meter to track and measure the pH value of the solution until the pH is adjusted to 4.5. Then, continue to add 0.2 g of polyethylene glycol 6000 to the solution under magnetic stirring and stir until completely dissolved to obtain an electrochemical deposition solution.

[0121] S3. Use the gas diffusion layer substrate pretreated in step S1 as the working electrode to construct a three - electrode system, and perform an electrodeposition reaction in the electrodeposition solution obtained in step S1 to obtain an oxygen evolution electrode loaded with a layered hydroxide catalyst.

[0122] Use the pretreated nickel felt substrate as the working electrode, a graphite rod as the counter electrode, and an Ag / AgCl electrode as the reference electrode for constant - voltage chrono - electrodeposition. The deposition conditions are a voltage of - 1V vs Ag / AgCl and a deposition time of 300 s. After the deposition is completed, take out the working electrode and rinse it with deionized water and ethanol for 10 min respectively, and then dry it naturally to obtain an oxygen evolution electrode loaded with a NiFe layered hydroxide catalyst.

[0123] Comparative Example 3

[0124] An experimental configuration method for an electrodeposition solution of an oxygen evolution electrode loaded with a high - entropy layered hydroxide catalyst, comprising the following steps:

[0125] S1. Pretreat the gas diffusion layer substrate.

[0126] Immerse a nickel felt substrate with a size of 5 cm×5 cm in 1M hydrochloric acid for 10 min, wash away the residual hydrochloric acid on the surface with deionized water, soak it in ethanol and ultrasonically clean it for 10 min, and then take it out and bake it in an oven at 60 °C for 30 min to obtain a pretreated nickel felt substrate.

[0127] S2. Mix hydrolyzable transition metal element salts, surfactants, and pH regulators with water to obtain an electrodeposition solution.

[0128] Weigh 14.54 g of nickel nitrate hexahydrate, 12.55 g of manganese nitrate tetrahydrate, 14.55 g of cobalt nitrate hexahydrate, and 9.94 g of ferrous chloride tetrahydrate into 500 ml of deionized water respectively, and stir well until completely dissolved. Under magnetic stirring conditions, add potassium acetate powder to the solution in small amounts and multiple times. During this process, use a pH meter to track and measure the pH value of the solution until the pH is adjusted to 7. During the adjustment process, it is found that a large amount of flocculent precipitate precipitates, and further electrodeposition cannot be carried out.

[0129] Comparative Example 4

[0130] An experimental configuration method for an electrodeposition solution of an oxygen evolution electrode loaded with a high - entropy layered hydroxide catalyst, comprising the following steps:

[0131] S1. Pretreat the gas diffusion layer substrate.

[0132] Soak a nickel felt substrate with a size of 5 cm × 5 cm in 1 M hydrochloric acid for 10 min, wash away the residual hydrochloric acid on the surface with deionized water, soak it in ethanol and ultrasonically clean it for 10 min, take it out and bake it in an oven at 60 °C for 30 min to obtain a pretreated nickel felt substrate.

[0133] S2. Mix a hydrolyzable transition metal element salt, a surfactant, and a pH regulator with water to obtain an electrochemical deposition solution.

[0134] Weigh 14.54 g of nickel nitrate hexahydrate, 12.55 g of manganese nitrate tetrahydrate, 14.55 g of cobalt nitrate hexahydrate, and 9.94 g of ferrous chloride tetrahydrate into 500 ml of deionized water, and stir well until completely dissolved. Under magnetic stirring conditions, add potassium acetate powder to the solution in small portions and measure the pH value of the solution with a pH meter until the pH is adjusted to 10. During the adjustment process, a large amount of flocculent precipitate was found to precipitate, and further electrodeposition could not be carried out.

[0135] Comparative Example 5

[0136] A preparation method of an oxygen evolution electrode loaded with a high-entropy layered hydroxide catalyst, comprising the following steps:

[0137] S1. Pretreat the gas diffusion layer substrate.

[0138] Soak a nickel felt substrate with a size of 5 cm × 5 cm in 1 M hydrochloric acid for 10 min, wash away the residual hydrochloric acid on the surface with deionized water, soak it in ethanol and ultrasonically clean it for 10 min, take it out and bake it in an oven at 60 °C for 30 min to obtain a pretreated nickel felt substrate.

[0139] Weigh 7 mg of thiourea into 60 mL of deionized water, stir until dissolved, transfer it to a hydrothermal reactor, add the nickel felt substrate, and transfer it to an oven for hydrothermal reaction to sulfide it. React at 150 °C for 5 h to obtain a conductive substrate loaded with nickel sulfide. Thiourea is purchased from Shanghai Macklin Biochemical Co., Ltd., with a CAS number of 62-56-6 and a purity of LR grade.

[0140] S2. Mix a hydrolyzable transition metal element salt and a pH regulator with water to obtain an electrochemical deposition solution.

[0141] Weigh 14.54 g of nickel nitrate hexahydrate, 12.55 g of manganese nitrate tetrahydrate, 14.55 g of cobalt nitrate hexahydrate, and 9.94 g of ferrous chloride tetrahydrate into 500 ml of deionized water, and stir well until completely dissolved. Under magnetic stirring conditions, add potassium acetate powder to the solution in small portions and measure the pH value of the solution with a pH meter until the pH is adjusted to 4.5 to obtain an electrochemical deposition solution.

[0142] S3. Using the gas diffusion layer substrate loaded with nickel sulfide pretreated in step S1 as the working electrode, a three - electrode system is constructed, and an electrodeposition reaction is carried out in the electrodeposition solution obtained in step S1 to obtain an oxygen evolution electrode loaded with a high - entropy layered hydroxide catalyst.

[0143] Using the pretreated nickel felt substrate as the working electrode, a graphite rod as the counter electrode, and an Ag / AgCl electrode as the reference electrode for constant - voltage chrono - electrodeposition, the deposition conditions are a voltage of - 1V vs Ag / AgCl and a deposition time of 300 s. After the deposition is completed, the working electrode is taken out and rinsed with deionized water and ethanol for 10 min respectively, and then dried naturally to obtain an oxygen evolution electrode loaded with a NiFeCoMn high - entropy layered hydroxide catalyst.

[0144] Figure 2 It is a schematic diagram of the crystal lattice structure of the high - entropy layered hydroxide catalyst shown in Example 1. The loaded high - entropy layered hydroxide catalyst has a two - dimensional layered nanostructure. The chemical formula of the high - entropy layered hydroxide catalyst can be expressed as M1M2…M n (OH) x (An) y ·mH2O (M1, M2, …M n are different transition metal elements; An is an intercalated anion, and the specific type depends on the hydrolyzable transition metal element salt; n is the number of types of transition metal elements, x is the normalized number of bonded hydroxide ions, y is the normalized number of intercalated anions, and m is the normalized number of hydrated water molecules). A high - entropy system is formed by introducing four or more transition metal elements.

[0145] Figure 3 It is the X - ray diffraction (XRD) pattern of an oxygen evolution electrode loaded with a high - entropy layered hydroxide catalyst provided in Example 1. Among them, JCPDS NO.51 - 0463 and JCPDS NO.04 - 0850 are X - ray diffraction standard cards issued by the Joint Committee on Powder Diffraction Standards, corresponding to the NiFe LDH structure and the elemental Ni substrate respectively. The positions of the diffraction peaks of the high - entropy layered hydroxide catalyst prepared in Example 1 can correspond one by one to the standard cards. The three strongest peaks correspond to the three characteristic crystal planes of the LDH structure, namely the (003), (006), and (012) crystal planes, indicating that the sample prepared in Example 1 has an LDH structure, and the relatively wide characteristic peak width indicates that the crystallinity of the material itself is not high.

[0146] Figure 4 It is the scanning electron micrograph of the oxygen evolution electrode loaded with the high - entropy layered hydroxide catalyst provided in Example 1. As Figure 4As shown, the high-entropy layered hydroxide catalyst particles are in the shape of regular nanoflowers. The layered structure of the orderly stacked LDH is conducive to obtaining a high specific surface area and good mechanical strength, increasing the catalytic sites of the material, helping to enhance the surface activity of the catalyst material, and further enhancing the adsorption capacity for water molecules.

[0147] Figure 5 Figure 4 is the FESEM EDS-mapping image of the oxygen evolution electrode loaded with the high-entropy layered hydroxide catalyst provided in Example 1. Table 1 shows the elemental mass percentages and atomic percentages corresponding to the FESEM EDS-mapping image. From Figure 5 Figure 4 and Table 1, it can be seen that the elements O, Mn, Ni, Fe, and Co are uniformly distributed on the material surface. Within the error range, it can be considered that the content ratios of each transition metal element are within the specified range at the mesoscopic and microscopic levels, effectively indicating the uniform growth of the material and the characteristics of the high-entropy elemental composition.

[0148] Table 1 Elemental mass percentages and atomic percentages corresponding to the FESEM EDS-mapping image

[0149] Element Line type Wt% At% Mn K-line series 10.27 10.74 Fe K-line series 31.75 32.66 Co K-line series 34.14 32.28 Ni K-line series 23.84 23.32 Total amount / 100.00 100.00

[0150] Figure 6 Figure 5 is the XPS image of each element of the oxygen evolution electrode loaded with the high-entropy layered hydroxide catalyst provided in Example 1. The fitting results show that in the lattice structure, Ni and Co elements tend to combine with -OH functional groups more. The peak positions of Ni 2p orbit and Co2p orbit are 855.8 eV (Ni 2p 3 / 2 ), 873.8 eV (Ni 2p 1 / 2 ), 781.1 eV (Co 2p 3 / 2 ), and 797.1 eV (Co 2p 1 / 2 ), respectively, which can correspond to the orbital peaks of Ni / Co hydroxide. While Mn and Fe elements tend to combine to form -OOH structures, and their orbital peak positions are located at 641.7 eV (Mn2p 3 / 2 ), 653.1 eV (Mn 2p 1 / 2 ), 711.6 eV (Fe 2p 3 / 2 ), and 725.1 eV (Fe 2p 1 / 2 ), respectively, which can correspond to the characteristic orbital peaks of Mn / Fe hydroxides. The valence states corresponding to each element are Ni 2+ , Mn 2+ , Fe 3+ , and Co 2+ , further illustrating the high-entropy component composition of the LDH catalyst and the corresponding functional group structure.

[0151] Figure 7 Linear sweep voltammetry (LSV) test curves of the oxygen evolution electrodes of the supported high-entropy layered hydroxide catalysts provided for Examples 1-7. It can be seen from Figure 7 that during the OER reaction process, the electrode potentials of the oxygen evolution electrodes of each example to reach a current density of 1000 mA cm -2 are 1.56 V (Example 1), 1.58 V (Example 2), 1.55 V (Example 3), 1.58 V (Example 4), 1.57 V (Example 5), 1.60 V (Example 6), and 1.57 V (Example 7), respectively, indicating that all the oxygen evolution electrodes have good catalytic activity.

[0152] Figure 8 Linear sweep voltammetry (LSV) test curves of the supported oxygen evolution electrodes provided for Example 1 and Comparative Examples 1, 2, and 5. It can be seen from Figure 8 that during the OER reaction process, the lowest electrode potential of the oxygen evolution electrode of the supported high-entropy layered hydroxide catalyst to reach a current density of 1000 mA cm -2 is only 1.56 V (Example 1), while the electrode potentials of the other comparative examples to reach a current density of 1000 mA cm -2 are 1.60 V (Comparative Example 1), 1.67 V (Comparative Example 2), and 1.57 V (Comparative Example 5), respectively, indicating that the preparation scheme of the oxygen evolution electrode of the supported high-entropy layered hydroxide catalyst has great catalyst performance advantages compared with other electrode preparation schemes.

[0153] Figure 9 Stability test curves of the oxygen evolution electrodes of the supported high-entropy layered hydroxide catalysts provided for Examples 1-7. It can be seen from Figure 9 that the oxygen evolution electrodes provided in each example can stably cycle for more than 500 h at a current density of 10000 A m -2 during the overall water splitting process (1 M KOH, 80 °C), indicating that the oxygen evolution electrodes have good catalytic stability.

[0154] Figure 10 Stability test curves of the supported oxygen evolution electrodes provided for Example 1 and Comparative Examples 1, 2, and 5. It can be seen from Figure 10 that during the overall water splitting process, the oxygen evolution electrode of the supported high-entropy layered hydroxide catalyst can reach 10000 A m -2It can be stably cycled for more than 500 h under the current density (1 M KOH, 80 °C). Under the same overall hydrolysis conditions, the oxygen evolution electrode provided in Comparative Example 1 without adding a surfactant during the deposition process has insufficient stability, and the oxygen evolution electrodes provided in Comparative Example 2 and Comparative Example 5 have relatively poor performance and stability. It shows that the preparation scheme of the oxygen evolution electrode loaded with the high-entropy layered hydroxide catalyst has a great advantage in catalyst stability compared with other electrode preparation schemes.

[0155] Although the present invention has been described in detail above with general descriptions, specific embodiments and experiments, based on the present invention, some modifications or improvements can be made, which are obvious to those skilled in the art. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection required by the present invention.

Claims

1. A method for preparing an oxygen evolution electrode loaded with a high entropy layered hydroxide catalyst, characterized in that: The following steps are involved: S1. Pre-treating the gas diffusion layer substrate; S2, adding water to a hydrolyzable transition metal element salt, a surfactant, and a pH adjuster to obtain an electrochemical deposition solution, wherein the hydrolyzable transition metal element salt contains four or more transition metal elements; S3, using the gas diffusion layer substrate pretreated in step S1 as a working electrode to construct a two-electrode or three-electrode system, and performing an electrodeposition reaction in the electrochemical deposition solution obtained in step S1 to obtain an oxygen evolution electrode loaded with a high entropy layered hydroxide catalyst.

2. The method for preparing an oxygen evolution electrode loaded with a high entropy layered hydroxide catalyst according to claim 1, characterized in that: In step S1, the pretreatment steps are: immersing the gas diffusion layer substrate in hydrochloric acid, washing with water, immersing in ethanol and performing ultrasound, and drying, and the pretreatment is completed.

3. The method for preparing an oxygen evolution electrode loaded with a high entropy layered hydroxide catalyst according to claim 1, characterized in that: In step S1 , the gas diffusion layer substrate includes nickel felt, nickel foam, titanium felt, or titanium foam.

4. The method for preparing an oxygen evolution electrode loaded with a high entropy layered hydroxide catalyst according to claim 1, characterized in that: In step S2, the hydrolyzable transition metal element salt includes nitrate, chloride, sulfate, acetate, polyacid, and the transition metal element is selected from at least four of manganese, iron, cobalt, nickel, copper, zinc, chromium, magnesium, aluminum, vanadium, titanium, rhodium, molybdenum, tungsten, lanthanum, cerium, and ruthenium.

5. The method for preparing an oxygen evolution electrode loaded with a high entropy layered hydroxide catalyst according to claim 4, characterized in that: The molar content of each transition metal is 10% to 40%.

6. The method for preparing an oxygen evolution electrode loaded with a high entropy layered hydroxide catalyst according to claim 1, characterized in that: In step S2, the surfactant includes polyethylene glycol, sodium lauryl sulfate, polyvinyl pyrrolidone, and hexadecyltrimethylammonium bromide.

7. The method for preparing an oxygen evolution electrode loaded with a high entropy layered hydroxide catalyst according to claim 1, characterized in that: In step S2, the pH adjuster includes potassium acetate, sodium acetate, potassium citrate, sodium citrate, potassium oxalate, and sodium aminoacetate; The pH of the electrochemical deposition solution is 4.0-6.

0.

8. The method for preparing an oxygen evolution electrode loaded with a high entropy layered hydroxide catalyst according to claim 1, characterized in that: In step S2, the molar mass ratio of the hydrolyzable transition metal element salt to the surfactant is 1 mol: 1-10 g; The concentration of the hydrolyzable transition metal element salt is 0.05 to 0.5 M; The concentration of the surfactant is 0.2-2 g / L.

9. The method for preparing an oxygen evolution electrode loaded with a high entropy layered hydroxide catalyst according to claim 1, characterized in that: In step S3, when constructing a two-electrode system, the counter electrode used is a graphite electrode or a metal platinum electrode, the electrodeposition process is a constant current timing method, the current is 80 to 140 mA / cm, and the electrodeposition time is 200 to 1000 s; When constructing a three-electrode system, the reference electrode used is an Ag / AgCl electrode, the electrodeposition process is a constant voltage timing method, the voltage is -0.9 to -1.5 V, and the electrodeposition time is 200 to 1000 s.

10. An oxygen evolution electrode loaded with a high entropy layered hydroxide catalyst, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Transition metal sulfide composite hydroxide electrode preparation method and application thereof

    CN114921803A